Parameter Optimization of CLAHE Method and Unsharp Mask Filter for Historic Image Quality Improvement - Hidayat, Jhoni; Harahap, Nurmahendra; Fitriani, Ayu; Syafriwel, Syafriwel; Faisal, Ahmad; Rizki, Mhd Fahmi Syawali (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
Historical images, such as old documentary photographs, ancient maps, manuscripts, or printed archives, are an important part of cultural and scientific heritage that provide a visual record of the past. Many available historical images have poor image quality because camera technology at that time was still in its infancy. This study examines the optimization of the combination of CLAHE (Contrast Limited Adaptive Histogram Equalization) and Unsharp Masking to improve the quality of historical images that have poor contrast, noise, and faded details. The approach includes preprocessing (greyscale image), CLAHE parameter optimization (clip limit) with a range of 0.01, 0.02, 0.03, 0.04, 0.05, and the Unsharp Mask method with a radius parameter of 1 and an amount parameter of 0.8. The clip limit parameter will be found that has better performance. To evaluate performance, the objective metrics Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) are used. Based on the criteria of the smallest MSE and the highest PSNR, the results showed that a clip limit of 0.01 was the most optimal parameter. This configuration proved effective in increasing contrast, sharpening detail, and minimizing noise, thus improving the quality of historical image restoration.